Recent Trends and Future Prospects in Electric Vehicle Technologies: A Comprehensive Review - Usman, Habib Muhammad; Sharma, Nirma Kumari; Joshi, Deepak Kumar; Kaushik, Aditya; Saminu, Sani (Kathmandu University Journal of Science, Engineering and Technology, 2024)
In addressing sustainability challenges within the transportation sector, the integration of electric vehicles (EVs) with renewable energy sources, notably solar and wind power, presents a promising solution. This comprehensive review delves into recent advancements and trends in EV technologies, covering crucial areas such as battery innovations, charging infrastructure, vehicle design, and market dynamics. Various EV technologies, including Plug-in Hybrid Electric Vehicles (PHEVs), battery-based EVs, Solar-powered EVs, and solar-wind hybrid EVs, are meticulously examined, with a particular focus on the feasibility and efficacy of solar-wind hybrid solutions. The review extends to battery technologies, emphasizing advancements in lithium-ion batteries and emerging chemistries like solid-state and lithium-sulfur batteries, which address barriers to EV adoption through enhanced energy density, charging efficiency, and cost-effectiveness. Additionally, the review scrutinizes the expansion of charging infrastructure, encompassing fast-charging stations, wireless charging technologies, and initiatives integrating smart grids, all aimed at providing convenient and efficient charging solutions to alleviate range anxiety and bolster EV attractiveness. Economic considerations, including initial investments, operational savings, and government incentives, are thoroughly analyzed alongside environmental benefits such as reduced greenhouse gas emissions and air pollution. Furthermore, a critical examination of the regulatory and policy framework supporting EVs sheds light on future policy directions, tax incentives, and regulatory measures. Real-world case studies showcasing successful implementations of solar-wind hybrid EV projects underscore their effectiveness and multifaceted impacts across diverse geographical areas. In conclusion, this review underscores the recent trends in EV technologies, emphasizing the feasibility and benefits of solar-wind hybrid EVs in achieving minimal emissions and incentivizing sustainable transportation practices.